Analisis Implementasi Nilai Dasar Ekonomi Islam pada Kinerja Pedagang Pasar Tradisional - Mukti, Titania (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2022)
Commerce in Islam is a lawful economic activity with the limitations of the Shari'a such as the basic values ​​of Islamic economics that must be obeyed. Pakem Kaliurang Traditional Market is a market where all traders who sell are Muslim. The location of the market is also close to the Indonesian Islamic university where traders have a fairly religious environment and should be able to implement the basic values ​​of Islamic economics in trading activities, but the economic conditions in the country are often changing and the urge to get the most profit from these activities Entrepreneurship sometimes makes traders tempted to commit fraud. The purpose of this study is to analyze the practice of the basic values ​​of Islamic economics, namely monotheism, justice, caliphate, nubuwah, and ma'ad on the performance of traders in the Pakem Kaliurang traditional market. The research location is Pakem Market, Sleman Yogyakarta. This type of research is descriptive qualitative. The source of the data used is primary data collected by interviewing 10 traders in the traditional market of Kaliurang. Traders interviewed were selected randomly and represented different types of goods sold. The results showed that not all basic values ​​of Islamic economics were applied in the performance of traders. Only the basic values ​​of caliphate and ma'ad are optimally practiced in everyday life.